Change in the bio-uptake of soil phthalates with increasing mulching years: Underlying mechanism and response to temperature rise. (10th March 2021) - Wang, Shuhan; Yu, Hanxia; Xi, Beidou; Tian, Zaifeng; Wang, Guoan; Tan, Wenbing
Abstract: Plastic mulch, which is widely used in agricultural production, releases phthalates to soil–plant systems and thus may pose potential human health risks. There is a growing concern of whether or how the phthalate bio-uptake varies with increasing mulching years, and what is the underlying mechanism and how this variation responds to global warming. Here, we used one of the most common leafy vegetables, spinach, as the research object and presented a pioneering investigation of this variation and mechanism and a prediction of the response of this variation to global warming. Phthalate concentrations in spinach increased first and then decreased after approximately 17 mulching years, suggesting that although phthalates accumulate in vegetables in the early stage of mulching, they decline after a decade. This change in spinach was mainly attributed to phthalate changes in bulk soil pore water with mulching years. Coarse sand fraction contributed 93% of phthalates in pore water. In addition, this study showed that the mean concentrations of BDP and DEHP in the soil under film mulching were 0.16 mg kg −1 and 0.46 mg kg −1, respectively, which were far below the U.S. soil cleanup criteria. Furthermore, the concentrations of DBP and DEHP in bulk soil increased first and then reached a relatively stable state after 20 mulching years. The above results are all good news, suggesting that film mulching is a clean and safe agricultural production technology. Our experiment of increasing temperature by 10 °C showed that increased temperature caused phthalates to increase in soil pore water extracted from both bulk soil and each soil fraction, and this increase became increasingly significant with mulching years. Thus, global warming is expected to promote the phthalate bio-uptake, and such effect will become more pronounced with increasing mulching years and thus must be paid attention. Graphical abstract: Image 1 Highlights: Bio-uptake of DBP and DEHP increased first and then decreased after 17 mulching years. Coarse sand made a major contribution to the DBP and DEHP in soil pore water. Increased temperature caused DBP and DEHP to increase in soil pore water. Increase of DBP and DEHP in soil pore water can be induced by warming.